2016
DOI: 10.1002/adom.201600303
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Tunable Goos–Hänchen Effect with Graphene in the Terahertz Regime

Abstract: Goos–Hänchen (G–H) effect is of great interest in the manipulation of optical beams. However, it is still fairly challenging to attain efficient controls of the G–H shift for diverse applications. Here, a mechanism to realize tunable G–H shift in the terahertz regime with electrically controllable graphene is proposed. Taking monolayer graphene covered epsilon‐near‐zero metamaterial as a planar model system, it is found that the G–H shifts for the orthogonal s‐polarized and p‐polarized terahertz beams at obliq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
57
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(57 citation statements)
references
References 55 publications
0
57
0
Order By: Relevance
“…Also, we have shown that HRTEM can further provide information about particle size distribution and lattice fringe of the carbon nanotubes and related catalysts [77][78][79][80][81][82][83][84][85][86][87][88][89]. The controllable synthesis of carbon nanotubes with tailored properties is certainly a challenge for researchers thanks to their valuable applications in several fields.…”
Section: Introductionmentioning
confidence: 98%
“…Also, we have shown that HRTEM can further provide information about particle size distribution and lattice fringe of the carbon nanotubes and related catalysts [77][78][79][80][81][82][83][84][85][86][87][88][89]. The controllable synthesis of carbon nanotubes with tailored properties is certainly a challenge for researchers thanks to their valuable applications in several fields.…”
Section: Introductionmentioning
confidence: 98%
“…Moving one step forward to modulate amplitude and phase simultaneously is more challenging. The Goos–Hänchen shift can be utilized for achieving frequency‐dependent dispersion . Metamaterials are still a popular candidate for narrowband polarization switching .…”
Section: Introductionmentioning
confidence: 99%
“…In this work, by utilizing the unique constraint of constant fields within zero‐index medium (ZIM, with permittivity or/and permeability near zero), we propose to realize CPA via the photonic doping of ZIM with absorptive defects. The concept and theory of “photonic doping” of an epsilon‐near‐zero (ENZ) medium, i.e.…”
Section: Introductionmentioning
confidence: 99%